Mewujudkan Kepastian Hukum Pendaftaran Hak Milik Atas Tanah untuk mencegah Timbulnya Sengketa Tata Usaha Negara - Johamran Pransisto; Kairuddin Karim; Muhammad Akbar Fhad Syahril (Jurnal Litigasi Amsir, 2022)
The implementation of the handling and settlement of state administrative disputes, especially those related to the registration of property rights at the State Administrative Court, can be measured by the level of effectiveness and success based on the decision of the state administrative court which has permanent legal force. its power, to the extent that the Defendant has acted upon it. The results of the research at the Makassar Administrative Court showed that 38 decisions on land disputes that had permanent legal force, only 24 decisions were followed up, while the other 14 decisions were not implemented. As the administrator of state administration, he should implement state administrative decisions that have permanent legal force in order to realize legal certainty and orderly implementation of land registration, especially the registration of property rights over land and in addition, the state administrative body or official must know the existence of judicial institutions, including implementing decision. judiciary which already has permanent legal force, so that it can contribute to the effectiveness of the administration of justice, especially the state administrative court.